Анализа укорељености нивоа ПДК4, НЛРП3 и ПТЕН у серуму код оштећења миокарда уз сепсу: Нивои серума PDK4, NLRP3 и PTEN приликом срчаног оштећења уз сепсу - Fang, Zebin; Li, Xiaoxia; Ou, Zhenfei; Wang, Jimu; Lin, Ke-Ji; Ye, Shujia (Journal of Medical Biochemistry, 2025)
Objective: To explore the correlations between the levels of serum pyruvate dehydrogenase kinase 4 (PDK4), NOD-like receptor protein 3 (NLRP3), and phosphatase and tensin homolog (PTEN) deleted on chromosome 10 and myocardial injury indicators as well as prognosis in patients with sepsis.Methods: A total of 355 patients who were first diagnosed with sepsis and admitted to our hospital from September 2022 to September 2024 were included. Depending on whether they suffered myocardial damage, the patients were split into two groups: the septic myocardial injury (SIMI) group (225 patients) and the simple sepsis group (130 patients). According to their survival outcomes after 28 days of treatment, the patients were divided into two groups: the death group (56 patients) and the survival group (169 patients). The levels of serum PDK4, NLRP3 and PTEN were detected via real-time fluorescence quantitative PCR (qRT‒PCR). An automatic biochemical analyzer was used to measure the levels of myoglobin (Mb), cardiac troponin I (cTnI), creatine kinase isoenzyme (CK-MB), and heart-type fatty acid binding protein (H-FABP). The Pearson correlation coefficient method was used to analyze the relationships between serum PDK4, NLRP3, and PTEN levels and myocardial injury indicators in SIMI patients. Cox regression analysis was employed to examine the variables affecting SIMI patients' prognoses.Results: The levels of serum PDK4, NLRP3, PTEN, CK-MB, cTnI, Mb and H-FABP in the SIMI group were significantly greater than those in the simple sepsis group (P
Keywords: Сепсис-индуцирана миокардна повреда; Piruvat dehidrogenaza kinaza 4 (PDK4); Протеин сличан Нод-рецептору 3 (NLRP3); Homolog proteina; Прогностичка корелација